The woman who changed her brain : and other inspiring stories of pioneering brain transformation - Arrowsmith-Young, Barbara (Free Press, 2012)
The founder of the Arrowsmith Program shares how she overcame severe learning disabilities by developing brain exercises to combat neurological challenges, discussing what her achievements reveal about the potential for shaping the human brain.